Essential Oil and Hydrophilic Antibiotic Co-Encapsulation in Multiple Lipid Nanoparticles: Proof of Concept and In Vitro Activity against Pseudomonas aeruginosa - Rayhane Ben-Khalifa (MDPI AG, 2021)
In the worldwide context of an impending emergence of multidrug-resistant bacteria, this research combined the advantages of multiple lipid nanoparticles (MLNs) and the promising therapeutic use of essential oils (EOs) as a strategy to fight the antibiotic resistance of three Pseudomonas aeruginosa strains with different cefepime (FEP) resistance profiles. MLNs were prepared by ultrasonication using glyceryl trioleate (GTO) and glyceryl tristearate (GTS) as a liquid and a solid lipid, respectively. Rosemary EO (REO) was selected as the model EO. REO/FEP-loaded MLNs were characterized by their small size (~110 nm), important encapsulation efficiency, and high physical stability over time (60 days). An assessment of the antimicrobial activity was performed using antimicrobial susceptibility testing assays against selected P. aeruginosa strains. The assays showed a considerable increase in the antibacterial property of REO-loaded MLNs compared with the effect of crude EO, especially against P. aeruginosa ATCC 9027, in which the minimum inhibitory concentration (MIC) value decreased from 80 to 0.6 mg/mL upon encapsulation. Furthermore, the incorporation of FEP in MLNs stabilized the drug without affecting its antipseudomonal activity. Thus, the ability to co-encapsulate an essential oil and a hydrophilic antibiotic into MLN has been successfully proved, opening new possibilities for the treatment of serious antimicrobial infections.